An emerging view on vascular fibrosis molecular mediators and relevant disorders: from bench to bed - Hua, Rongxuan; Gao, Han; He, Chengwei; Xin, Shuzi; Wang, Boya; Zhang, Sitian; Gao, Lei; Tao, Qiang; Wu, Wenqi; Sun, Fangling; Xu, Jingdong (Frontiers in Cardiovascular Medicine, 2023)
Vascular fibrosis is a widespread pathologic condition that arises during vascular remodeling in cardiovascular dysfunctions. According to previous studies, vascular fibrosis is characterized by endothelial matrix deposition and vascular wall thickening. The RAAS and TGF-β/Smad signaling pathways have been frequently highlighted. It is, however, far from explicit in terms of understanding the cause and progression of vascular fibrosis. In this review, we collected and categorized a large number of molecules which influence the fibrosing process, in order to acquire a better understanding of vascular fibrosis, particularly of pathologic dysfunction. Furthermore, several mediators that prevent vascular fibrosis are discussed in depth in this review, with the aim that this will contribute to the future prevention and treatment of related conditions.